JOINT REPORT ON STATUS OF FIRE SERVICE ENDORSEMENTS OF H.R. 4497 (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Philip Schaenanman to Susan Stuntz and Karen Fernicola regarding endorsements from fire services for the bill H.R. 4497. Lists endorsements by state and whether they are assigned to Tridata or Peter Sparber.